Prevention and Management of Delirium in the Intensive Care Unit - Mart, Matthew F.; Williams Roberson, Shawniqua; Salas, Barbara; Pandharipande, Pratik P.; Ely, E. Wesley (Seminars in Respiratory and Critical Care Medicine, 2020)
Delirium is a debilitating form of brain dysfunction frequently encountered in the intensive care unit (ICU). It is associated with increased morbidity and mortality, longer lengths of stay, higher hospital costs, and cognitive impairment that persists long after hospital discharge. Predisposing factors include smoking, hypertension, cardiac disease, sepsis, and premorbid dementia. Precipitating factors include respiratory failure and shock, metabolic disturbances, prolonged mechanical ventilation, pain, immobility, and sedatives and adverse environmental conditions impairing vision, hearing, and sleep. Historically, antipsychotic medications were the mainstay of delirium treatment in the critically ill. Based on more recent literature, the current Society of Critical Care Medicine (SCCM) guidelines suggest against routine use of antipsychotics for delirium in critically ill adults. Other pharmacologic interventions (e.g., dexmedetomidine) are under investigation and their impact is not yet clear. Nonpharmacologic interventions thus remain the cornerstone of delirium management. This approach is summarized in the ABCDEF bundle (Assess, prevent, and manage pain; Both SAT and SBT; Choice of analgesia and sedation; Delirium: assess, prevent, and manage; Early mobility and exercise; Family engagement and empowerment). The implementation of this bundle reduces the odds of developing delirium and the chances of needing mechanical ventilation, yet there are challenges to its implementation. There is an urgent need for ongoing studies to more effectively mitigate risk factors and to better understand the pathobiology underlying ICU delirium so as to identify additional potential treatments. Further refinements of therapeutic options, from drugs to rehabilitation, are current areas ripe for study to improve the short- and long-term outcomes of critically ill patients with delirium.
Keywords: delirium; ABCDEF bundle; cognitive impairment; critical illness; intensive care; early mobility; antipsychotics; dementia